Effects of salicylic acid on the quality of fresh-cut Chinese water chestnuts - Liu Yu; Keyan Lu; Yang Yi; Limei Wang; Wenfu Hou; Youwei Ai; Hongxun Wang; Ting Min (Journal of Agriculture and Food Research)
Fresh-cut Chinese water chestnuts (CWCs) are susceptible to yellowing and browning, which degrades their overall quality and palatability. Therefore, there is an urgent need to develop effective methods and techniques to maintain their color and freshness. This study aimed to analyze the mechanisms underlying the effects of salicylic acid (SA) treatment on the quality deterioration of fresh-cut CWCs during storage. Soaking fresh-cut CWCs in 3.5 mmol of SA for 40 min and subsequently storing them delayed the yellowing of fresh-cut CWCs. This treatment also mitigated weight loss and loss of soluble solids. In addition, SA treatment enhanced the accumulation of total phenolics by promoting the activity of phenylalanine ammonia-lyase (PAL) and concomitantly suppressing the activities of browning-associated enzymes (PPO and POD). Meanwhile, the application of SA increased the activity of antioxidant enzymes such as SOD and CAT while limiting the accumulation of reactive oxygen species (ROS). Moreover, SA treatment delayed the yellowing and browning of fresh-cut CWCs by down-regulating the expression of CwCHS1, CwCHS2, CwCHS3, CwCHI1, CwCHI2, CwMYC2, CwERF5-like, and CwERF069-like and by limiting the synthesis of flavonoids. Finally, SA treatment upregulated the expression of the ERF transcription factors CwAP2/ERF, CwERF1, CwERF4A, and CwERF4B and concurrently promoted ethylene biosynthesis, which, in turn, accelerated the senescence and microbial growth of fresh-cut CWCs.